Comparative Analysis of the Anthropometric Parameters Among the Ethnic Groups of Karachi - Mahrukh Kamran; Rabia Rahan; Sahar Mubeen; Munazza Suharwardy Obaid; Hira Ahmed; Shazia Fahmi (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: Objectives of this study were to determine the average height, weight, BMI, BSA and LBM among the different ethnic groups that exist in population of Karachi and to determine whether these anthropometric parameters vary significantly among the ethnic groups. Methods: It was a prospective cross-sectional study that was carried out at Ziauddin University and Hospital from March 2012 to May 2014. In this study healthy volunteers aged 21 years and above were recruited. Height, weight, body mass index (BMI), body surface area (BSA) and lean body mass (LBM) of healthy volunteers were taken into account through the standard protocol after following inclusion and exclusion criteria. The study was approved by the ethical review committee IRB and BASR committee of Ziauddin University Clifton Karachi. Results: Greatest height 169.5 ± 9.1 cm and weight 73.4 ± 15.4 kg was found in Pathans. Highest body mass index (BMI) 27.1 ± 4.3 kg/m2, body surface area (BSA)1.8 ± 0.2 m2 and lean body mass (LBM) 52.6 ± 9.6 kg was found in Hazarah group. Weight, BMI and BSA was found to vary significantly among the ethnic groups (p<0.05) while height and LBM was found to vary insignificantly among the ethnic groups. Anthropometric parameters vary significantly between the genders among all the ethnic groups. Beside BMI all the anthropometric parameters were significantly greater in males. Conclusion: Anthropometric parameters noted among the ethnic groups in Karachi were very close to the studies done in the different provinces of Pakistan. In almost all the ethnic groups, BMI males were found to have significantly greater anthropometric parameters as compare to the females.